2013
DOI: 10.1111/mec.12461
|View full text |Cite
|
Sign up to set email alerts
|

NiphargusThiothrix associations may be widespread in sulphidic groundwater ecosystems: evidence from southeastern Romania

Abstract: Niphargus is a speciose amphipod genus found in groundwater habitats across Europe. Three Niphargus species living in the sulphidic Frasassi caves in Italy harbour sulphur-oxidizing Thiothrix bacterial ectosymbionts. These three species are distantly related, implying that the ability to form ectosymbioses with Thiothrix may be common among Niphargus. Therefore, Niphargus–Thiothrix associations may also be found in sulphidic aquifers other than Frasassi. In this study, we examined this possibility by analysing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…The presence of 11 epigean freshwater amphipod species or species complexes previously recognized in Romania, and the two presently synonymized subspecies of G. balcanicus, was confirmed by our data and recent literature. The only species not encountered during our field survey was N. hrabei; however, a recent study reported it in south-eastern Romania (Flot et al 2014), confirming its presence after more than 50 years.…”
Section: Resultsmentioning
confidence: 64%
“…The presence of 11 epigean freshwater amphipod species or species complexes previously recognized in Romania, and the two presently synonymized subspecies of G. balcanicus, was confirmed by our data and recent literature. The only species not encountered during our field survey was N. hrabei; however, a recent study reported it in south-eastern Romania (Flot et al 2014), confirming its presence after more than 50 years.…”
Section: Resultsmentioning
confidence: 64%
“…Niphargus thrives in all types of subterranean waters, from shallow hypotelminorheic ones (i.e., shallow seeps filled with groundwater; Fišer et al 2010) to epikarst (Sket 1981), sinking streams and phreatic lakes (Trontelj et al 2012). Niphargid amphipods have also been noted for their dominant presence in hypogenic caves, i.e., caves that result from limestone dissolution by hydrogen sulfide arising from deep reservoirs (Latella et al 1999;Sarbu et al 2000;Forti et al 2002;Flot et al 2010Flot et al , 2014. These sulfidic caves are of particular interest from an ecological viewpoint: instead of sunlight (photoautotrophy) or allochthonous organic material (organoheterotrophy), they derive their energy from inorganic chemical compounds (chemoautotrophy; Sarbu et al 1996Sarbu et al , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This genus is taxonomically demanding and its species richness is far from being completely described. The morphology of niphargids is not a very good proxy for the phylogenetic relationships among these species (Fišer et al 2008;Trontelj et al 2012;Flot et al 2014), and cryptic species (i.e., species that are nearly indistinguishable from a morphological point of view but possess distinctive DNA sequences) appear common in this group ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations